The environmental licensing of hydroelectrics and the interface with migratory fish and aquaculture in Brazil - Vidal, Mayara Venturini [UNESP]; Batlouni, Sergio Ricardo [UNESP] (Boletim do Instituto de Pesca, 2022)
In this review, we present a background on the Brazilian Federal Legislation on the environmental licensing of hydroelectric plants focusing on the procedure of the repair of environmental damage caused by dams to migratory fish. To that end, the Brazilian electrical matrix was first addressed, thus highlighting the significant contribution of the energy produced by hydroelectric projects. To better contextualize the characteristics of the legislation, separate sections concerning illustrative reports of the effects of dams on migratory fish and the current panorama of aquaculture in Brazil and in the world were included. In this review, we also present a discussion on the specific legislation concerning a mitigation measure, the “fish restocking programs,” which have the potential to promote fishing and aquaculture, but still lack a scientific basis on their effectiveness and correct application. An assessment of this historical process in Brazil indicates that different mitigation measures imposed to obtain operating licenses by hydroelectric plants vary among different hydroelectric projects and that this heterogeneity in the conditions imposed may have effects (of unknown proportions) on local fish communities. Considering the absence of a specific device foreseen in the law that requires the owner or concessionaire of dams in watercourses to provide for fish restocking programs or specific ichthyofauna conservation programs, the issue seems to depend on the discretion of the licensing agency to demand that the hydroelectric plant operators carry out the reintroduction of fish in their reservoirs. This review concludes that there are political and scientific issues to be debated and explored in order to improve public policies on this topic of extreme relevance for society.
O licenciamento ambiental de hidrelétricas e a interface com os peixes migratórios e a aquicultura no Brasil
Keywords: fish ladder; hydroelectric plants; public policies; rheophilic species